Effect of Shading on Seasonal Varition of Some Macro-nutrients in Camarosa Strawberry - Ersoy, Beril; Demirsoy, Husnu (Asian Journal of Chemistry, 2010)
This study is aimed to determine the effects of shading on variation of mineral elements as seasonal. The treatments included greenhouse check, no shade and constant shading (CS). Nitrogen, phosphorus, potassium and calcium in root, crown and leaf of strawberry camarosa were determined. In the study, N and P contents in the plant parts were generally lower, the plants in greenhouse check having more crown size and leaf area and a greater root volume, probably as a result of dilution. Potassium content in crown and root generally reduced prior to spring while it increased with starting of growth period. Calcium content increased in spring and summer with increasing temperature. Phosphorus and calcium content were more than that of root and crown. In addition, it was shown that shading does not affect the K and Ca content in leaf and crown.